A high-rate cathode material hybridized by in-site grown Ni–Fe layered double hydroxides and carbon black nanoparticles. Issue 13 (11th March 2016) - Chen, Shuzhen; Mao, Min; Liu, Xi; Hong, Shiyu; Lu, Zhouguang; Sang, Shangbin; Liu, Kaiyu; Liu, Hongtao
Abstract : In-site grown 3D flower-like Ni–Fe layered double hydroxides and carbon black nanoparticles were hydrothermally hybridized and showed great potential as an alternative high-rate alkaline cathode. Abstract : A facile hydrothermal fabrication was applied to hybridize in-site grown flower-like Ni–Fe layered double hydroxides (Ni–Fe LDHs) and carbon black (CB) nanoparticles. The well-conductive CB particles were dispersed homogeneously onto the petals of the Ni–Fe LDH flowers via a combination of electrostatic forces and ripening growth, and remarkably promoted the charge-transfer capability of the LDHs. The hybridized Ni–Fe LDH/CB composite electrode exhibited excellent rate performance that retained both a high capacity and steady cycle life at a large charge–discharge current, and was highly competitive serving as a high-rate alkaline battery cathode.